Investigating isovector properties of finite nuclei through neutron stars - Kanakis-Pegios, Alkiviadis; Divaris, M.; Moustakidis, Charalambos C. (HNPS Advances in Nuclear Physics, 2026)
The symmetry energy is a key quantity for the structure of finite nuclei and the bulk properties of neutron stars. Therefore, its investigation has special significance in nuclear astrophysics, especially given the uncertainty that presents in the high density region and the large error in data from corresponding experiments. A way to get an indication about the behavior of symmetry energy in high densities is to examine it in the context of neutron stars. The recent observations of gravitational waves emitted from binary neutron star mergers provide useful information on characteristics such as the radius and the tidal deformability, i.e. two quantities that are in direct relation to the symmetry energy. Our work aims to examine the symmetry energy under this point of view and specifically obtain constraints on the structure of finite nuclei. In this effort, we deploy a methodology that is based on parameterization of the equation of state of asymmetric and symmetric nuclear matter through the introduction of a parameter called η=(K0L2)1/3, which combines the incompressibility K0 and the slope parameter L. In fact, the parameter η serves as a regulator of the stiffness of the equation of state. This quantity affects both the properties of finite nuclei and the properties of neutron stars, where the isovector interaction plays a significant role. Hence, we expect that the obtained constraints, through the values of η, will provide insights on the properties of neutron stars and finite nuclei vice versa. Our investigation proposes a simple and self-consistent method to examine the effects of η on both kind of properties, which led us to derive constraints on the latter systems by using recent experiments (PREX-2) and astrophysical observables (observations from LIGO/VIRGO collaboration).